SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN JURUSAN BAGI SISWA SMA N 8 MERANGIN DENGAN METODE SIMPLE ADDITIVE WEIGHTED (SAW): DECISION SUPPORT SYSTEM, SIMPLE ADDITIVE WEIGHTED (SAW), MAJORS SELECTION - Purnama, Fery (FORTECH (Journal of Information Technology), 2017)
Selection department is one of the problems that often occur in National Senior High School 8 Merangin due to selectionof majors for students frequent errors, whichoften students have majors that are not appropriate to the abilities and interests often students, therefore, a decision support system an important role inprtant in the selection of majors students so as to help the students and the school in reaching a decision (majors) for students. which expected to give the right decision and the best results for new students.